Do self-created metacognitive prompts promote short- and long-term effects in computer-based learning environments? - Engelmann, Katharina; Bannert, Maria; Melzner, Nadine (Research and practice in technology enhanced learning, 2021)
Students must engage in self-regulated learning in computer-based learning environments; however, many students experience difficulties in doing so. Therefore, this study aims to investigate self-created metacognitive prompts as a means of supporting students in their learning process and improving their learning performance. We conducted an experimental study with a between-subject design. The participants learned with self-created metacognitive prompts ( n = 28) or without prompts ( n = 29) in a hypermedia learning environment for 40 min while thinking aloud. In a second learning session (stability test), all participants learned about a different topic without prompts. The results showed no clear effect of the self-created metacognitive prompts on the learning process and performance. A deeper analysis revealed that students’ prompt utilization had a significant effect on performance in the second learning session. This study contributes to the research investigating how students can be supported in ways that enhance their learning process and performance.